ANALISIS YURIDIS KEWENANGAN HAKIM PRAPERADILAN DALAM PERINTAH PENETAPAN TERSANGKA BARU DITINJAU DARI HUKUM ACARA PIDANA INDONESIA - Dino Setiawan; Zulfikar Jayakusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Adding pretrial objects to the Constitutional Court's decision No. 21 / PUU-XII / 2014 is a form of refinement of the functions of pretrial institutions. One of them was the addition of the object of determining the suspect in the realm of pretrial, which should have been able to strengthen the protection of human rights from the forced efforts of law enforcers to seek legal certainty and justice. The order to determine the suspect by the judge in the decision Number 24 / Pid.Pra / 2018 / PN.Jkt.Sel until now is still a pros and cons because it is not included in the pretrial object as stated in Article 1 point 10 Junto 77 KUHAP or MK Decision No. . 21 / PUU-XII / 2014, so that judges are deemed to have left their authority. The purpose of writing this thesis, namely, First, to find out whether the judge has the authority to order the determination of suspects in pretrial decisions No. 24 / Pid.Pra / 2018 / PN.Jkt.Sel, Second, whether there are legal remedies that can be taken after the pretrial ruling Number 24 /Pid.Pra/2018/PN.Jkt.Sel about the order to determine a new suspect by the South Jakarta District Court, Third, How is the validity of the order to determine a new suspect by a pretrial judge in decision Number 24 / Pid.Pra / 2018 / PN.Jkt.Sel in terms of the Indonesian criminal justice system.This type of research can be classified in the type of normative juridical research, which is precisely research that studies how to synchronize law, because in this study the authors use literary legal materials or secondary data only as data in this study, data sources used, primary legal materials, materials secondary law and tertiary legal material.From the results of research and discussion of the problem there are three main things that can be concluded. First, the pretrial judge in decision Number 24 / Pid.Pra / 2018 / PN.Jkt.Sel must be guided by Article 1 point 10 of Junto 77 of the Criminal Procedure Code that the judge still does not have the authority to order the investigator to determine a suspect against a person. Second, after the pretrial verdict Number. 24 / Pid.Pra / 2018 / PN.Jkt.Sel it is possible to submit ordinary legal remedies and also extraordinary legal remedies for the reason that the pretrial proceedings are quick and simple. This was also strengthened after the issuance of Supreme Court Regulation (PERMA) Number 4 of 2016. Third, the order to determine suspects in a pretrial ruling Number. 24 / Pid.Pra / 2018 / PN.Jkt.Sel was a violation of the provisions stipulated by the law Number 8 of 1981 which becomes the guideline in the procedure for determining a suspect. Because, the judge ordered the determination of suspects who were not his authority. Then it can be said that the decision violates the concept of the justice system - the process of law.Keywords: Pretrial, Determination of the suspect, Due Process of Law.